Komposisi Aset, Fleksibilitas Keuangan, dan Intensitas Utang terhadap Valuasi Pasar Perusahaan Sektor Industri di ASEAN - Angga Anggasmara Putra; Nelly Nur Apandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study investigates whether asset structure, liquidity and leverage explain the market value of industrial firms in selected ASEAN capital markets. The analysis is motivated by the observation that positive macroeconomic growth in ASEAN does not necessarily translate into homogeneous stock-market valuation, particularly in asset-intensive sectors. Using a balanced panel of 438 industrial firms listed in Indonesia, Malaysia and Singapore over 2022-2024, this study applies explanatory quantitative research and panel-data regression. Firm market value is proxied by closing stock price, while asset structure, liquidity and leverage represent internal fundamentals that may signal productive capacity, short-term financial flexibility and financing risk. Model selection tests indicate that the Fixed Effect Model is superior to both the Common Effect Model and the Random Effect Model. Because the preliminary diagnostic tests indicate heteroskedasticity, the final estimates are obtained using White diagonal standard errors and covariance. The findings show that asset structure, liquidity and leverage have positive and statistically significant effects on market value. The model is also significant simultaneously, with an adjusted R-squared of 0.9605. The results support signaling theory, resource-based view and trade-off theory by showing that investors respond positively to productive asset capacity, adequate liquidity and debt financing when these fundamentals are interpreted as value-creating rather than risk-deteriorating signals. The study contributes to the literature by offering cross-country evidence from ASEAN industrial firms and by using a market-based valuation proxy rather than relying solely on accounting-based performance indicators.